Recommendations for cardiovascular disease prevention in women: An Indian perspective - Zakia Khan; Sarita Rao; Ritu Bhatia; Saumitra Ray; Jamshed J Dalal (Journal of the Practice of Cardiovascular Sciences, 2023)
Cardiovascular disease (CVD) is one of the leading causes of death in women. On an average, coronary artery disease develops 10 years later in women than men, but they represent the majority of patients when age above 75 years is considered. Men and women share most of the classic cardiovascular risk factors, but the relative importance of each risk factor may be gender specific. This review explores the recommendations for the management of cardiovascular risk and CVD prevention in women in the Indian clinical setting based on multiple advisory board meetings conducted with cardiology experts across India. The experts concurred that women have distinct patterns of ischemic heart disease (IHD) and that the presence of traditional risk factors, female-specific risk factors, and nontraditional risk variables may add to the increasing risk of IHD. Transition to postmenopausal status is associated with a worsening coronary heart disease risk profile in women. Evidence suggests that both traditional and novel cardiovascular risk factors are often under recognized and undertreated in women. Several female-specific risk factors such as preterm delivery, preeclampsia, gestational diabetes, and polycystic ovary syndrome are not included in primary prevention nor are they routinely considered in a cardiovascular assessment at the clinical level. Understanding and good diagnostic tools are necessary to evaluate the different pathophysiological aspects and early detection of CVD in women.